Mouse Spexin: (II) Functional Role as a Satiety Factor inhibiting Food Intake by Regulatory Actions Within the Hypothalamus - Wong, Matthew K. H.; Chen, Yuan; He, Mulan; Lin, Chengyuan; Bian, Zhaoxiang; Wong, Anderson O. L. (Frontiers in Endocrinology, 2021)
Spexin (SPX) is a pleiotropic peptide with highly conserved protein sequence from fish to mammals and its biological actions are mediated by GalR2/GalR3 receptors expressed in target tissues. Recently, SPX has been confirmed to be a novel satiety factor in fish species but whether the peptide has a similar function in mammals is still unclear. Using the mouse as a model, the functional role of SPX in feeding control and the mechanisms involved were investigated. After food intake, serum SPX in mice could be up-regulated with elevations of transcript expression and tissue content of SPX in the glandular stomach but not in other tissues examined. As revealed by immunohistochemical staining, food intake also intensified SPX signals in the major cell types forming the gastric glands (including the foveolar cells, parietal cells, and chief cells) within the gastric mucosa of glandular stomach. Furthermore, IP injection of SPX was effective in reducing food intake with parallel attenuation in transcript expression of NPY, AgRP, NPY type 5 receptor (NPY5R), and ghrelin receptor (GHSR) in the hypothalamus, and these inhibitory effects could be blocked by GalR3 but not GalR2 antagonism. In agreement with the central actions of SPX, similar inhibition on feeding and hypothalamic expression of NPY, AgRP, NPY5R, and GHSR could also be noted with ICV injection of SPX. In the same study, in contrast to the drop in NPY5R and GHSR, SPX treatment could induce parallel rises of transcript expression of leptin receptor (LepR) and melanocortin 4 receptor (MC4R) in the hypothalamus. These findings, as a whole, suggest that the role of SPX as a satiety factor is well conserved in the mouse. Apparently, food intake can induce SPX production in glandular stomach and contribute to the postprandial rise of SPX in circulation. Through GalR3 activation, this SPX signal can act within the hypothalamus to trigger feedback inhibition on feeding by differential modulation of feeding regulators (NPY and AgRP) and their receptors (NPY5R, GHSR, LepR, and MC4R) involved in the feeding circuitry within the CNS.